Laboratory atlas of anatomy and physiology - Eder, Douglas J. (McGraw-Hill Higher Education, 2004)
This full color atlas is intended to effectively supplement the A&P laboratory course and aid students in their studies. Eder's high-quality visuals, in combination with its unique tables (terms and definitions; as well as tables describing the origin, insertion, action, and innervation of muscles) make it a valuable supplement in any lab course. It illustrates the dissection structures as they actually exist so that students will be able to easily recognize the parts when they are dissecting or taking an exam